2021
DOI: 10.1155/2021/4759461
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Measurement of Parameters of Quality of Life in Informal Settlements Surrounding of Tehran Metropolis

Abstract: Quality of life is a concept used to describe the development of the welfare of society, and improving the quality of life is one of the most important goals of governments around the world. Informal settlements, as one of the most vulnerable urban areas, are always in unfavorable conditions in terms of various social, economic, and physical indicators. Therefore, the main purpose of this study is to investigate the status of various quality of life indicators in informal settlements around the metropolis of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…The past literature has revealed that only 13% of the world's populace lived in urban areas before the commencement of the industrial era, but these numbers have increased dramatically in the 20th and 21st centuries (Das, 2015). However, the world population that reached till 8 billion (Gan, et al 2023) has only a small share of 3.1 billion people that live in the rural settlements (Ghaderpour, 2021). As a result, metropolitan regions have received significant attention, financial assistance, and services that leaved the rural communities more impoverished.…”
Section: Introductionmentioning
confidence: 99%
“…The past literature has revealed that only 13% of the world's populace lived in urban areas before the commencement of the industrial era, but these numbers have increased dramatically in the 20th and 21st centuries (Das, 2015). However, the world population that reached till 8 billion (Gan, et al 2023) has only a small share of 3.1 billion people that live in the rural settlements (Ghaderpour, 2021). As a result, metropolitan regions have received significant attention, financial assistance, and services that leaved the rural communities more impoverished.…”
Section: Introductionmentioning
confidence: 99%
“…El objetivo de este trabajo consistió en proponer un índice alternativo de medición del desempeño económico de México. La motivación se fundamentó en proveer herramientas que coadyuvaran en las decisiones de política pública, porque, según Ghaderpour et al (2021), el mejoramiento en calidad de vida es primordial para las naciones. Y si los gobiernos consiguen atender satisfactoriamente las necesidades, esto fomentará el desarrollo de los países, y, por el contrario, si no se consigue, habrá tensiones sociales.…”
Section: Introductionunclassified